LITERASI EKONOMI, KESEHATAN DAN PENDIDIKAN DI CISATA KABUPATEN PANDEGLANG BANTEN - Musfiroh Nurlaili H; Rubiyanah Rubiyanah; Nurul Jamali (Jurnal Kommunity Online, 2020)
AbstractBased on the results of observations and field assessments, the main problem of the service location in Cisata District, Pandeglang Regency is tourism-based economic literacy, healthy life literacy for life expectancy is getting better and the growth of independent / underdeveloped villages. That's why it is important to carry out assistance efforts to encourage acceleration development and independence of local villagers. Namely, through literacy strengthening programs or illiteracy eradication, both reading, writing and arithmetic. This includes supporting a healthy environmental situation through the construction of public toilets / toilets and the provision of clean water (joint drilling of wells / villagers). As well as promoting tourism based on community local wisdom and natural beauty. The empowerment approach used is action research or Participatory Action Research (PAR). Of the three dimensions, namely economy, education and health, community empowerment actions show mixed results. There are optimal results for several programs such as community consultation and drilling for clean water. However, there are also some programs that are not yet optimal, such as lectures on economic empowerment of the ummah.Keywords: capital and literacy assistance; participatory action research; skills programsAbstrakBerdasarkan hasil pengamatan dan assessmen lapangan, yang menjadi masalah utama lokasi pengabdian di Kecamatan Cisata Kabupaten Pandeglang adalah melek perekonomian berbasis wisata, melek hidup sehat untuk usia harapan hidup semakin membaikdan pertumbuhan kemandirian desa terlambat/tertinggal.Oleh karena itulah penting melakukan upaya pendampingan untuk mendorong percepatan pembangunan dan kemandirian warga desa setempat. Yakni melalui program penguatan literasi atau pengentasan buta aksara, baik membaca, menulis dan berhitung. Termasuk mendukung situasi lingkungan hidup yang sehat melalui pembangunan WC/Toilet umum dan penyediaan air bersih (pengeboran sumur bersama/warga desa). Serta promosi wisata berbasis kearifan lokal masyarakat dan keindahan alam.Pendekatan pemberdayaan yang digunakan adalah riset aksiatau Participatory Action Research (PAR).Dari ketigalierasi, yakniekonomi, pendidikandankesehatan,aksi pemberdayaan masyarakat memperlihatkan hasil yang beragam. Terdapat hasil yang optimal untuk beberapa program seperti rembuk warga dan pengeboran air bersih. Namun terdapat pula beberapa program yang belum optimal, seperti ceramah pemberdayaan ekonomi ummat.Kata kunci: bantuan modal dan literasi;  participatory action research; program keterampilan